Effect of increasing doses of beta agonists on spirometric parameters, exercise capacity, and quality of life in patients with chronic airflow limitation. Issue 5 (May 1994) - Jaeschke, R; Guyatt, G H; Willan, A; Cook, D; Harper, S; Morris, J; Ramsdale, H; Haddon, R; Newhouse, M
Abstract : BACKGROUND--A study was undertaken to determine the impact of different doses of inhaled terbutaline on peak flow rates, spirometric parameters, functional exercise capacity, and quality of life in patients with chronic airflow limitation. METHODS--A double blind, randomised, placebo controlled, multiple crossover trial was conducted with treatment periods of one week. Patients with a clinical diagnosis of chronic airflow limitation and FEV1 below 70% predicted after administration of bronchodilator were recruited from secondary care respiratory practices, and the effect of 500, 1000, and 1500 micrograms inhaled terbutaline four times daily on spirometric parameters (FEV1, FVC), maximum inspiratory pressures, six minute walking distance, and health-related quality of life (Chronic Respiratory Disease Questionnaire, Quality of Well Being, Standard Gamble) was measured. RESULTS--Twenty five patients completed the trial. Peak flow rates and FEV1 showed statistically significant but clinically trivial improvement on the higher drug doses. Results of maximum inspiratory pressure measurements, walk test distance, and quality of life measures showed minimal differences on the different dosages, and none of the differences approached conventional statistical significance. CONCLUSIONS--Regular use of beta agonists in doses higher than two puffs four times a day is very unlikely to provide additional functional or symptomatic benefit to patients with chronic airflow limitation.